Culture and liberation exile writings, 1966-1985 - La Guma, Alex 1925-1985 (The Africa list, 2022)
One of South Africa's best-known writers during the apartheid era, Alex La Guma was a lifelong activist and a member of the South African Communist Party and the African National Congress. Persecuted and imprisoned by the South African regime in the 1950s and 60s, La Guma went into exile in the United Kingdom with his wife and children in 1966, eventually serving as the ANC's diplomatic representative for Latin America and the Caribbean in Cuba. Culture and Liberation captures a different dimension of his long writing career by collecting his political journalism, literary criticism, and other short pieces published while he was in exile. This volume spans La Guma's political and literary life in exile through accounts of his travels to Algeria, Lebanon, Vietnam, Soviet Central Asia, and elsewhere, along with his critical assessments of Paul Robeson, Nadine Gordimer, Maxim Gorky, Alexander Solzhenitsyn, and Pablo Neruda, among other writers. The first dedicated collection of La Guma's exile writing, Culture and Liberation restores an overlooked dimension of his life and work, while opening a window on a wider world of cultural and political struggles in Africa, Asia, and Latin America during the second half of the twentieth century